2016
DOI: 10.1136/sextrans-2016-052609
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability of self-sampled screening for HPV DNA: a systematic review and meta-analysis

Abstract: The overall acceptability of self-sampled cervical screening, coupled with economic and effective care, provides opportunities for expanding screening services. Importantly, this can provide a creative screening alternative for women who do not participate in traditional cytological screening, and may ultimately reduce health disparities and prevent cervical disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
194
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(227 citation statements)
references
References 35 publications
(28 reference statements)
29
194
3
1
Order By: Relevance
“…A recent meta-analysis of 37 studies including 18,516 women revealed that HPV-DNA sampling screening was highly accepted compared with clinician's sampling. In the future, the importance of self-collection method will increase, especially from the viewpoint of cost-effectiveness and expansion of screening services [101]. Therefore, HPV-DNA testing by self-sampling has the potential to become the mainstream in cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 37 studies including 18,516 women revealed that HPV-DNA sampling screening was highly accepted compared with clinician's sampling. In the future, the importance of self-collection method will increase, especially from the viewpoint of cost-effectiveness and expansion of screening services [101]. Therefore, HPV-DNA testing by self-sampling has the potential to become the mainstream in cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is similarly divided, such that some authors believe that self-sampling should be an option available to all eligible women (not just non-responders) 39,40 , while others suggest that self-sampling is appropriate only as a strategy to reach "non-compliant" women 24,41 , and yet others argue that self-sampling is not the best way to reach under-or never-screened groups 22,42 . Recent evidence syntheses suggest that most women find self-sampling preferable to clinician-collected sampling 23,43 . Other systematic reviews found that self-sampling could increase cervical screening coverage in under-or never-screened women 24 , though some authors observed similar uptake rates in opt-in scenarios 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Human papillomavirus testing can be performed on a vaginal sample that women can collect themselves-"self-sampling"-which might be an attractive option to overcome some of the barriers to provider-administered screening [21][22][23][24][25] . Though there is high-quality evidence internationally to support self-collected sampling in population-based programs, only the Netherlands and Australia have implemented a self-sampling strategy as part of their population-based program.…”
Section: Introductionmentioning
confidence: 99%
“…Not 188 surprisingly, cervical cancer rates are higher in women who have not been screened 189 according to the recommended guidelines (Lam et al 2017), with cervical cancer 190 mortality rates being the highest in underscreened populations (Benard et al 2014;191 Musselwhite et al 2016 sampling over clinician sampling (Nelson et al 2017). 201…”
Section: Hc2 Hpv Assay and Several Pcr Amplification-based Tests Sucmentioning
confidence: 99%